2016
DOI: 10.1007/s12035-016-9908-0
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Transient Receptor Potential Ankyrin 1 Channel Deregulates Emotion, Learning and Memory, Cognition, and Social Behavior in Mice

Abstract: The transient receptor potential ankyrin 1 (TRPA1) channel is a non-selective cation channel that helps regulate inflammatory pain sensation and nociception and the development of inflammatory diseases. However, the potential role of the TRPA1 channel and the underlying mechanism in brain functions are not fully resolved. In this study, we demonstrated that genetic deletion of the TRPA1 channel in mice or pharmacological inhibition of its activity increased neurite outgrowth. In vivo study in mice provided evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…Likewise, another group showed that in TRPA1 receptor gene-deleted mice behavioral deficits and neuroinflammation were less severe in a transgenic mouse model of Alzheimer's disease [24]. The same group also later demonstrated that the loss of TRPA1 is associated with decreased anxiety-like behavior and improved performance in spatial memory and social discrimination tests [25].Based on these prior data we focused on further elucidating the role of TRPA1 receptors in the cuprizone model. In the present study, the effects of cuprizone in the corpus callosum were studied in mGFAP-driven conditional TRPA1 knockout mice.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Likewise, another group showed that in TRPA1 receptor gene-deleted mice behavioral deficits and neuroinflammation were less severe in a transgenic mouse model of Alzheimer's disease [24]. The same group also later demonstrated that the loss of TRPA1 is associated with decreased anxiety-like behavior and improved performance in spatial memory and social discrimination tests [25].Based on these prior data we focused on further elucidating the role of TRPA1 receptors in the cuprizone model. In the present study, the effects of cuprizone in the corpus callosum were studied in mGFAP-driven conditional TRPA1 knockout mice.…”
mentioning
confidence: 95%
“…Likewise, another group showed that in TRPA1 receptor gene-deleted mice behavioral deficits and neuroinflammation were less severe in a transgenic mouse model of Alzheimer's disease [24]. The same group also later demonstrated that the loss of TRPA1 is associated with decreased anxiety-like behavior and improved performance in spatial memory and social discrimination tests [25].…”
mentioning
confidence: 95%
“…A previous study reported that ME inhibited the voltage-gated sodium Na V 1.7 channels, which underlies its antinociceptive and anesthetic actions (Wang et al, 2015). Additionally, ME is an agonist of the TRPA1 channel (Moon et al, 2015); blockade or genetic ablation of the TRPA1 channel decreases anxietylike behaviors in mice (de Moura et al, 2014;Lee et al, 2017). Therefore, ME activation of TRPA1 channels may increase anxiety-like behaviors in mice.…”
Section: Discussionmentioning
confidence: 98%
“…It is best known as a sensor for environmental irritants and endogenous electrophilic compounds that are formed during oxidative stress [103] and evoke pain, cold, itch and inflammation [104], however it probably also has other undiscovered functions. In support of this assumption, along with decreased responses to peripheral pain models and temperature changes, global TRPA1 knockouts are hyperactive [105], and have sensory dysregulation, cognitive dysfunction, and motor deficits proposed to result from a decrease in myelination [106].…”
Section: A C C E P T E Dmentioning
confidence: 94%